Shaping the Future: Greece’s Innovation Centers as Hubs for Sustainable Practices in Constructionist Education (Constructionism Conference Proceedings, 2025)
This article explores the transformative role of Greece’s Innovation Centers (ICs) in advancing constructionist education and sustainability. By serving as collaborative hubs that connect schools, local communities, universities, and businesses, the centers foster STEM learning and promote environmental stewardship by utilizing cutting-edge technologies, such as Extended Reality (XR), Artificial Intelligence (AI), and robotics, to create immersive and engaging educational experiences. Through hands-on learning, Eco-Friendly Maker Spaces, and Sustainability-Themed STEM Modules, students develop critical thinking, creativity, and problem-solving skills while addressing real-world environmental challenges. The article also highlights the challenges of resource constraints, teacher training, and curriculum integration, proposing effective strategies such as partnerships and blended learning approaches to overcome them. Ultimately, the synergy between constructionist education and sustainability at the ICs equips future leaders to navigate complex environmental issues and fosters a culture of responsibility and innovation, preparing students to become proactive agents of change in their communities.